DEMON Acoustic Ship Signature Measurements in an Urban Harbor - Chung, Kil Woo; Sutin, Alexander; Sedunov, Alexander; Bruno, Michael (Advances in acoustics and vibration, 2011)
Detection, classification, and tracking of small vessels are important tasks for improving port security and the security of coastal and offshore operations. Hydroacoustic sensors can be applied for the detection of noise generated by vessels, and this noise can be used for vessel detection, classification, and tracking. This paper presents recent improvements aimed at the measurement and separation of ship DEMON (Detection of Envelope Modulation on Noise) DEMON acoustic signatures in busy harbor conditions. Ship signature measurements were conducted in the Hudson River and NY Harbor. The DEMON spectra demonstrated much better temporal stability compared with the full ship spectra and were measured at distances up to 7 km. The combination of cross-correlation and methods allowed separation of the acoustic signatures of ships in busy urban environments.